Pengaruh Pembelajaran Online Terhadap Pembentukan Karakter Pada Siswa Kelas X IPA SMA Negeri 9 Manado - Shallomitha Zefanya Aror; Rinna Y Kasenda; Deklay Nainggolan; Meisie L Mangantes (Prodi Bimbingan Konseling Universitas Negeri Manado, 2022)
This study aims to determine the effect of online learning to developing character students at SMA Negeri 9 Manado. This research was conducted using quantitative methods. The sample of 53 students at SMA Negeri 9 Manado for the 2021/2022 academic year. Data was collected on a Likert scale. Data analysis techniques using simple linear regression analysis with the help of the SPSS 24 for Windows computer program. The results showed that there was an effect of online learning on character building in students, the regression equation Y=64,896 + 0,964 X with a quantitative withdrawal comparison of the two variables was 1:0,964. This comparison shows that if there is an increase of one time/unit in the online learning variable (X), there will be an increase of 0.964 in the student character formation variable (Y). The regression equation is significant or not, it will be tested using the Fcount value at a significant level of 0.05. It means that Ha is accepted and H0 is rejected. The conclusion is that the hypothesis which reads that there is an effect of online learning on character formation in grade X science students at SMA Negeri 9 Manado is accepted and significant. This means that the higher the level of online learning will have a positive and significant effect on character building in students.